The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.ajhg.2018.12.014
|View full text |Cite|
|
Sign up to set email alerts
|

De Novo SOX4 Variants Cause a Neurodevelopmental Disease Associated with Mild Dysmorphism

Abstract: SOX4, together with SOX11 and SOX12, forms group C of SRY-related (SOX) transcription factors. They play key roles, often in redundancy, in multiple developmental pathways, including neurogenesis and skeletogenesis. De novo SOX11 heterozygous mutations have been shown to cause intellectual disability, growth deficiency, and dysmorphic features compatible with mild Coffin-Siris syndrome. Using trio-based exome sequencing, we here identify de novo SOX4 heterozygous missense variants in four children who share de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 56 publications
2
31
1
1
Order By: Relevance
“…Also, SOX3 missense variant was detected in proband with mild intellectual disability ( Jelsig et al, 2018 ). Furthermore, it was found that SOX4 heterozygous missense variants cause neurodevelopmental disease ( Zawerton et al, 2019 ). On the other side, SOX5 haploinsufficiency and its loss of function variant have been found in probands with intellectual disability ( Lamb et al, 2012 ; Schanze et al, 2013 ; Nesbitt et al, 2015 ).…”
Section: Sox Transcription Factors and Neurodevelopmental Disordersmentioning
confidence: 99%
“…Also, SOX3 missense variant was detected in proband with mild intellectual disability ( Jelsig et al, 2018 ). Furthermore, it was found that SOX4 heterozygous missense variants cause neurodevelopmental disease ( Zawerton et al, 2019 ). On the other side, SOX5 haploinsufficiency and its loss of function variant have been found in probands with intellectual disability ( Lamb et al, 2012 ; Schanze et al, 2013 ; Nesbitt et al, 2015 ).…”
Section: Sox Transcription Factors and Neurodevelopmental Disordersmentioning
confidence: 99%
“…Additionally, there have been four cases of CSS where heterozygous mutations in SOX4 have been identified. Like SOX11, these mutations were within the HMG domain and variant proteins were unable to bind DNA and activate target gene expression (Zawerton et al, 2019). Little is known about the roles of SoxC factors in the context of craniofacial development.…”
Section: Coffin-siris Syndromementioning
confidence: 99%
“…Genes in the BAF (Brahma/BRG1-associated factor) complex are essential in chromatin remodeling. Pathogenic variants in this complex have been associated with a number of conditions, including Coffin-Siris syndrome (CSS, MIM 135900, ORPHA:1465), Nicolaides-Baraitser syndrome (NCBRS, MIM 601358) and other CSS-like conditions ( SOX4 ) [ 1 , 2 ]. A range of learning and developmental differences, organ-related anomalies, and variable physical and facial features typically characterize BAFopathies, a term that has been proposed in its description.…”
Section: Introductionmentioning
confidence: 99%